2015 IEEE International Conference on Computer Vision (ICCV) 2015
DOI: 10.1109/iccv.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Classifier Training to Minimize False Merges in Electron Microscopy Segmentation

Abstract: The prospect of neural reconstruction from Electron Microscopy (EM) images has been elucidated by the automatic segmentation algorithms. Although segmentation algorithms eliminate the necessity of tracing the neurons by hand, significant manual effort is still essential for correcting the mistakes they make. A considerable amount of human labor is also required for annotating groundtruth volumes for training the classifiers of a segmentation framework. It is critically important to diminish the dependence on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Compared to a CNN of the same architecture trained on all ground-truth images, our technique achieves slightly better segmentation accuracy. Our results corroborate well with past studies [3,7] that found that interactive training tends to produce a classifier that performs better for segmentation.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to a CNN of the same architecture trained on all ground-truth images, our technique achieves slightly better segmentation accuracy. Our results corroborate well with past studies [3,7] that found that interactive training tends to produce a classifier that performs better for segmentation.…”
Section: Introductionsupporting
confidence: 92%
“…[3] and Parag et.al. [7] also proposed methods for sparse selection of a subset of training examples and demonstrated their advantages for EM segmentation. However, the strong dependence of the random forest classifiers on hand-tuned features has the potential to limit their performances on images from different EM preparation/imaging techniques and, more generally, from other data modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of simultaneously considering all surrounding pixels and computing responses for the feature maps, RNN-based networks treat the pixels as a list or sequence with various routing rules and recurrently update each feature pixel. In fact, RNN-based membrane segmentation approaches are crucial for connected component labeling steps that can resolve false splits and merges during the post-processing of probability maps (Ensafi et al, 2014;Parag et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…Discovering the anatomical structure entails a 3D segmentation of EM volume. Numerous studies have addressed this task with many different approaches, we refer interested readers to [3] [4][5] [6] [7][8] [9] for further details. In order to unveil the connectivity, it is necessary to identify the locations and the direction of synaptic communications between two or more cells.…”
Section: Introductionmentioning
confidence: 99%